Efficient mannitol production by wild-type Lactobacillus reuteri CRL 1101 is attained at constant pH using a simplified culture medium - Ortiz, María Eugenia (2015)
Mannitol is a natural polyol with multiple industrial applications. In this work, mannitol production by Lactobacillus reuteri CRL 1101 was studied at free- and controlled-pH (6.0–4.8) fermentations using a simplified culture medium containing yeast and beef extracts and sugarcane molasses. The activity of mannitol 2-dehydrogenase (MDH), the enzyme responsible for mannitol synthesis, was determined. The effect of the initial biomass concentration was further studied. Mannitol production (41.5 ± 1.1 g/l), volumetric productivity (QMtl 1.73 ± 0.05 g/l h), and yield (YMtl 105 ± 11 %) were maximum at pH 5.0 after 24 h while the highest MDH activity (1.66 ± 0.09 U/mg protein) was obtained at pH 6.0. No correlation between mannitol production and MDH activity was observed when varying the culture pH. The increase (up to 2000-fold) in the initial biomass concentration did not improve mannitol formation after 24 h although a 2-fold higher amount was produced at 8 h using 1 or 2 g cell dry weight/l comparing to the control (0.001 g cell dry weight/l). Finally, mannitol isolation under optimum fermentation conditions was achieved. The mannitol production obtained in this study is the highest reported so far by a wild-type L. reuteri strain and, more interestingly, using a simplified culture medium.